Treatment and outcome of adult patients with acute asthma in emergency departments in Australasia, South East Asia and Europe: Are guidelines followed? AANZDEM/EuroDEM study. (25th February 2019) - Craig, Simon; Kuan, Win Sen; Kelly, Anne‐Maree; Van Meer, Oene; Motiejunaite, Justina; Keijzers, Gerben; Jones, Peter; Body, Richard; Karamercan, Mehmet A; Klim, Sharon; Harjola, Veli‐Pekka; Verschuren, Franck; et al.
Abstract: Objective: Asthma exacerbations are common presentations to ED. Key guideline recommendations for management include administration of inhaled bronchodilators, systemic corticosteroids and titrated oxygen therapy. Our aim was to compare management and outcomes between patients treated for asthma in Europe (EUR) and South East Asia/Australasia (SEA) and compliance with international guidelines. Methods: In each region, prospective, interrupted time series studies were performed including adult (age >18 years) patients presenting to ED with the main complaint of dyspnoea during three 72 h periods. This was a planned sub‐study that included those with an ED primary diagnosis of asthma. Data was collected on demographics, clinical features, treatment in ED, diagnosis, disposition and in‐hospital outcome. The results of interest were differences in treatment and outcome between EUR and SEA cohorts. Results: Five hundred and eighty‐four patients were identified from 112 EDs (66 EUR and 46 SEA). The cohorts had similar demographics and co‐morbidity patterns, with 89% of the cohort having a previous diagnosis of asthma. There were no significant differences in treatment between EUR and SEA patients – inhaled beta‐agonists were administered in 86% of cases, systemic corticosteroids in 66%, oxygen therapy in 44% and antibiotics in 20%. Two thirds of patients were discharged home from the ED. Conclusion: The data suggests that compliance with guideline‐recommended therapy in both regions, particularly corticosteroid administration, is sub‐optimal. It also suggests over‐use of antibiotics.